Deep-sea exploration of marine ecosystems – Knowledge and solutions for marine biodiversity - Rogers, Alex David; Ramirez Llodra, Eva (The International Hydrographic Review, 2025)
In honour of the centenary of The International Hydrographic Review (IHR) in 2023, Prof Dr Alex David Rogers was invited to contribute to the special Jubilee Issue* with a keynote article on the exploration of deep-sea biodiversity over the past 100 years and a look into the future of deep-sea exploration of marine ecosystems. As this was not possible in the Jubilee year, we are now publishing the manuscript. We review discoveries in deep-sea biodiversity since the establishment of the International Hydrographic Organisation in 1921. Over the last century it has been demonstrated that the deep sea harbours a great variety of habitats which host a large diversity of species rivalling that of other marine and terrestrial ecosystems. This was possible through the invention of quantitative sampling methods and deep-submergence technologies as well as advances in fields such as acoustics and marine navigation. Increasing human activities impacting the deep ocean now demand knowledge of the distribution of life in the deep sea is greatly improved through further exploration.